2001 Conference Proceedings of the 23rd Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2001.1019665
|View full text |Cite
|
Sign up to set email alerts
|

Animal-shaped toys as therapeutic tools for patients with severe dementia

Abstract: Abstract-An animal-shaped toy was provided as a therapeutic tool to patients with severe dementia during a therapeutic program and after dinner. The occupational therapist delivered three animal -shaped toys-a gorilla, a tiger and a dog-during the therapeutic program. These toys performed amusing actions. The occupational therapist observed the activities of the patients and classified them into six categories (no reaction, close observation, talking, clapping, patting the toy, taking care of the toy). The tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Thus, the alternative of replacing real animals with animal-shaped objects became an object of investigation (Nakajima et al, 2001 ). In recent years, social robots have been also used as reasonable substitutes for animals in therapy for people suffering from dementia (Wada et al, 2008 ; Shibata, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the alternative of replacing real animals with animal-shaped objects became an object of investigation (Nakajima et al, 2001 ). In recent years, social robots have been also used as reasonable substitutes for animals in therapy for people suffering from dementia (Wada et al, 2008 ; Shibata, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that there are therapeutic gains associated with the use of doll therapy for people with 'severe dementia' and that its use helped to reduce a range of behaviour that challenges, such as 'anxiety, aggression and wandering'. Nakajima et al (2001) engaged in a similar study in Japan using animalshaped toys instead of dolls. However, the authors state that they carried out this study in response to the practical difficulties of assessing the use of pet therapy in dementia and do not provide any theoretical underpinnings to their study, despite the results appearing favourable.…”
Section: Figure 2 'Babyloid' Dolls Have Eyelids and Mouths That Movementioning
confidence: 99%
“…Description of dolls used in practice Nakajima et al (2001) Three animal-shaped toys: a gorilla, a tiger and a dog Gibson (2005) 'Baby is a cute battery-operated doll purchased in the toy department of a local store'…”
Section: Studymentioning
confidence: 99%
“…Many ambient intelligence systems (e.g., Aarts, Hartwig & Schuurmans, 2001) include devices that monitor elderly persons. In settings where humans interact intensively with these systems, such as cuddle bots for dementia patients (e.g., Nakajima et al, 2001), the system can combine the data gathered from these devices with Silicon Coppélia to maintain a model of the emotional state of the user. This can enable the system to adapt the type of interaction to the user's needs.…”
Section: Applicationsmentioning
confidence: 99%